LAW ENFORCEMENT AS A METHOD OF PROVISION FOR NATIONAL TAX SECURITY - K. Maslov (Правоприменение, 2017)
УДК 342.5The place of law enforcement in the system of provision for national tax security is analyzed in the article. The author analyzes scientific approaches to the concept of national security as a generic term to the tax security, highlights its elements and contents.The author notes that the state, public and personal safety shouldn’t be opposed each other, but they should be considered as elements of a unified system of national securityFull and effective implementation of the rights and legitimate interests of citizens and their communities equally meets the needs of national security as the protection of the interests of the state as a whole.The author is convinced that national security and tax security in particular are achievable only in conditions of genuine state sovereignty. The characteristics of the forms of tax sovereignty, as well as classification of threats to tax sovereignty and tax security, are given in the article.The author's concepts of national security and tax security are given in the article as well as their tasks are defined. National tax security is defined by author as a level of development of public relations in the sphere of taxation, when the amount of collecting taxes corresponds to the number of planned tax revenues taking into account the need for full funding of all functions and tasks of the state and municipalities both in the current period and in the future.The interests of the tax security, of course, must be taken into account in the enforcement process in tax relations. The author describes the mechanism of the interdependence of the national tax security and law enforcement in tax relations. The ignoring of threats to tax security by tax enforcers reduces the level of security and does not meet the objectives of the implementation of the law in a sovereign state.